Barriers and enablers for group-based manual emptying services for onsite sanitation facilities in Nairobi, Kenya: a qualitative study - Tomoi, H.; Ingumba, B.B.; Simiyu, S.; Otteng, E.; Osewe, J.; Majiwa, Hamilton; Braun, L.; Cumming, O.; Moriyasu, T. (Elsevier, 2025)
Onsite sanitation, such as pit latrines, is essential to achieving universal access to safe sanitation, as outlined in Sustainable Development Goal target 6.2. However, manual emptying for pit latrines in low-income areas is often unhygienic, posing health and environmental risks. Enhancing the safety of these services increases costs, yet affordability for customers is essential. Thus, reducing service costs is a key priority. Group-based approach, where emptiers visit multiple toilets consecutively, has potential to improve both service efficiency and affordability. However, few studies have investigated its applicability to manual emptying. This paper aims to identify barriers and enablers for group-based manual emptying services in low-income neighbourhoods of Nairobi. We conducted 12 focus group discussions with landlords, tenants, and manual emptiers in the Korogocho informal settlement in Nairobi and interviewed 20 key informants from relevant sectors in Kenya. We identified five categories of barriers and enablers that affected general and group-based manual emptying: 1) funding, 2) expertise and equipment, 3) social and commercial habits, 4) physical conditions, and 5) regulatory systems. Of these, a norm that pits are not emptied until they get full, operating time constraints, fair and transparent pricing, and an organiser who can arrange group-based emptying from Category 3, and transport capacity from Category 4 specifically affected group-based manual emptying. Given that the barriers have a cascade structure, addressing some primary barriers such as capacity building and recognising manual emptiers’ role in the sanitation policies could be effective ways to ensure safe and affordable emptying services.